Coming back together: a qualitative survey study of coping and support strategies used by people to cope with extended difficulties after the use of psychedelic drugs - Robinson, Oliver C.; Evans, Jules; Luke, David; McAlpine, Rosalind; Sahely, Aneta; Fisher, Amy; Sundeman, Stian; Ketzitzidou Argyri, Eirini; Murphy-Beiner, Ashleigh; Michelle, Katrina; Prideaux, Ed (Frontiers in Psychology, 2024)
A growing body of literature is focused on understanding the extended difficulties individuals encounter after psychedelic experiences. Although existing research has explored the nature and predictors of these difficulties, a significant research gap exists in the exploration of coping strategies adopted by individuals in response. This study collected data from an diverse international cohort of 608 participants who had experienced difficulties that persisted for at least one day after a psychedelic experience. They provided written data on how they coped with these difficulties. The qualitative analysis of the written data on coping was conducted using Structured Tabular Thematic Analysis. It revealed a wide range of coping strategies employed at both individual and social levels. Predominant among individual strategies were meditation and prayer, followed by self-educational activities such as reading and journaling. The most prevalent forms of social coping involved seeking support from friends or family members, followed by obtaining assistance from a therapist or coach. Particular features of social coping were reported to be helpful such as feeling heard, feeling accepted and sharing similar experiences. These insights hold significant potential for designing therapeutic interventions and educational resources aimed at enhancing coping strategies for those experiencing extended difficulties after psychedelic use.